Investigating genome wide dna methylation in airway smooth muscle cells from asthmatic and non-asthmatic donors - Clifford, Rachel L.; Patel, J.K.; Shaw, D.E.; Knox, A.J.; Kobor, M.S. (BMJ Publishing Group, 2016)
Rationale: Genetic mechanisms fail to fully explain asthma pathogenesis and environmental factors are considered to play an important role. Environmental factors may lead to permanent changes in epigenetic patterns and contribute to asthma. Epigenetics is the study of heritable changes in gene expression that are not due to changes in DNA sequence. DNA methylation is a reversible modification of DNA structure in which a methyl group is added to cytosine residues. Parental smoking affects the methylation of buccal cell DNA from children and children with early onset wheeze have an altered blood DNA methylation profile to healthy individuals. No studies have compared DNA methylation profiles in the disease relevant cell type of airway smooth muscle (ASM) cells.